Comparative Analysis of QoE Multipath TCP Congestion Control LIA, CUBIC, and WVEGAS on Video Streaming - Fiqqih Maulana Susanto; Aji G. Putrada; Siti Amatullah Karimah (International Journal on Information and Communication Technology (IJoICT), 2021)
Transmission Control Protocol (TCP) is a type of protocol that allows a collection of computers to communicate and exchange data within a network. Nowadays electronic devices such as tablets, personal computers and smartphones can use more than one network at the same time, but this is not supported by the characteristics of TCP which can only use one path on the network. To solve this condition there are several new generations of standardized network protocols. Multipath TCP is a development of TCP, Multipath which is a new generation network protocol that allows traffic to use multiple paths in the network. In addition to being able to use multiple paths on multipath TCP, there are several congestion control algorithms including LIA, CUBIC and WVEGAS congestion control algorithms. Tests conducted in this study were to compare the performance of congestion control LIA, CUBIC and WVEGAS to improve the quality of video streaming. From the test results, CUBIC is better than WVEGAS and LIA because the QoS and QoE video streaming test for CUBIC in all testing environment has better results than others.